2022
DOI: 10.3390/ijms23084217
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Propranolol as a Repurposed Drug in Rare Vascular Diseases

Abstract: Rare Diseases (RD) are defined by their prevalence in less than 5 in 10,000 of the general population. Considered individually, each RD may seem insignificant, but together they add up to more than 7000 different diseases. Research in RD is not attractive for pharmaceutical companies since it is unlikely to recover development costs for medicines aimed to small numbers of patients. Since most of these diseases are life threatening, this fact underscores the urgent need for treatments. Drug repurposing consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…The β-adrenergic antagonist propranolol also increased IDE levels in an AD mouse model (Dobarro et al, 2013). Propanolol is used to treat hypertension, arrhythmias, essential tremor, and anxiety (Cuesta et al, 2022) and has been used…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The β-adrenergic antagonist propranolol also increased IDE levels in an AD mouse model (Dobarro et al, 2013). Propanolol is used to treat hypertension, arrhythmias, essential tremor, and anxiety (Cuesta et al, 2022) and has been used…”
Section: Discussionmentioning
confidence: 99%
“…The β‐adrenergic antagonist propranolol also increased IDE levels in an AD mouse model (Dobarro et al, 2013). Propanolol is used to treat hypertension, arrhythmias, essential tremor, and anxiety (Cuesta et al, 2022) and has been used to reduce disruptive behaviors in patients with AD and other dementias (Pauszek, 1991; Peskind et al, 2005; Shankle et al, 1995; Weiler et al, 1988). Also of relevance to AD, propranolol was recently found to have acetylcholinesterase‐inhibiting activity (Ciprés‐Flores et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the long use of propranolol mainly as a therapy for proliferating hemangioma, its action and efficiency are still questionable. Mulliken discovered that propranolol acts differently on different cell types based on hemangioma structure using histochemical methods [ 24 ], and Glowacki observed hemangioma cell heterogeneity in hemangioma cells. Hemangioma-derived progenitor/stem cells (HemSCs), mesenchymal stem cells (Hem-MSCs), endothelial progenitor cells (HemEPCs), endothelial cells (HemECs), and perivascular cells (Hem-pericytes) have all been isolated from hemangioma tissues in recent decades [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these mechanisms contributed to the successful use of propranolol in the treatment of infantile hemangiomas (IH) ( You et al, 2021 ; Cuesta et al, 2022 ). It has been shown that this indication is more effective than steroids, although patients treated with propranolol should be monitored due to the risk of recurrence and the possible need for re-treatment ( Frongia et al, 2021 ; You et al, 2021 ).…”
Section: Propranolol–an Old Drug With New Propertiesmentioning
confidence: 99%